Analisis Time Series Dan Cross Section Terhadap Kinerja Keuangan Sub Sektor Otomotif: PT Astra Internasional Tbk, PT Garuda Metalindo Tbk Dan PT Indomobil Sukses Internasional Tbk Tahun 2020-2022 - Rulis Setyowati; Vivi Ade Rivani; Yunita Budi A M; Cholis Hidayati (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze the financial performance in the automotive sector of PT Astra Internasional Tbk, PT Garuda Metalindo Tbk, and PT Indomobil Sukses Internasional Tbk during the 2020-2022 period. The analysis was carried out using qualitative descriptive research methods. Explaining that descriptive research is research that seeks to describe a symptom or event that is happening. The results showed that the financial performance of the three automotive companies improved in 2022 compared to 2020. This is indicated by an increase in financial ratios, such as liquidity ratio, activity ratio, solvency ratio, profitability ratio and market ratio. Based on Time Series and Cross Section Analysis, it can be concluded that PT Garuda Metalindo is a company that has high growth prospects than PT Astra Internasional Tbk and PT Indomobil Sukses Internasional Tbk.